2013
DOI: 10.1017/sjp.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Stress Scale (PSS): Normative Data and Factor Structure for a Large-Scale Sample in Mexico

Abstract: One of the most widely used scales for the evaluation of stress is the Perceived Stress Scale (PSS), and it has been adapted into different languages. However, few studies have presented normative data from large samples, and there do not appear to be any studies of the PSS that provide normative data based on large samples for Mexico. Thus, the goal of this study was to provide normative data regarding gender and different age groups for a sample of 1990 Mexican subjects to validate the factor structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 9 publications
7
41
1
7
Order By: Relevance
“…One, it was found that education students' stress levels were much higher than the general population reported in the normative data in the research of González-Ramírez et al (2013). This is consistent with the statement of Stallman (2010) that university students' stress levels were much higher than those of the general population (Stallman, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…One, it was found that education students' stress levels were much higher than the general population reported in the normative data in the research of González-Ramírez et al (2013). This is consistent with the statement of Stallman (2010) that university students' stress levels were much higher than those of the general population (Stallman, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Some researchers have posited that the negative-worded factor measures perceived helplessness or negative stress, and that the positive-worded factor measures perceived self-efficacy or positive stress (Reis, Hino, & Anez, 2010; Roberti, Harrington, & Storch, 2006). Despite robust empirical support for a two-dimensional structure, the factor distinction has been regarded as superficial and not meaningful (Carretero-Dios & Pérez, 2007; Cohen, 1988; González-Ramírez, Rodríguez-Ayán, & Hernández, 2013; Lee, 2012; Ramírez & Hernández, 2007), and a single summed PSS score is most often used in research and clinical contexts. Overall, there is little research on the validity or reliability for each of the two factors.…”
Section: Pss Factor Structurementioning
confidence: 99%
“…The populations that have been sampled for psychometric studies on the PSS have been university students and working populations (Lee, 2012). Some studies have examined the reliability and validity of the Spanish translated PSS, however samples have been specific to Mexico (González-Ramírez et al, 2013; Ramírez & Hernández, 2007) and Spain (Remor, 2006). Cronbach's alpha values for the PSS have ranged from .78 to .91 for English and Spanish versions (Lee, 2012; Remor, 2006).…”
Section: Pss Factor Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The validity of the three parts of the questionnaire was confirmed by a panel of experts, including three cardiologists, one interventionist, ten head nurses, and twenty nurses working at the coronary and post coronary units. The perceived stress questionnaire was designed by Kohn and Kamark (34). The Perceived Stress Scale (PSS) is the most widely used psychological instrument for measuring the perception of stress, which is a measure of the degree to which situations in one's life are appraised as stressful.…”
Section: Methodsmentioning
confidence: 99%